Simplifying solution space : enabling non-expert users to innovate and design with toolkits - Naik, Hari Suman (Springer Fachmedien Wiesbaden, 2017)
Hari Suman Naik takes the perspective of modular systems and investigates how to enable non-expert users to innovate and design, by simplifying toolkit solution space. New production technologies like digital fabrication and modular electronics along with appropriate toolkits can offer users a significant design flexibility to innovate solutions that meet their heterogeneous and sticky needs. The author contributes towards understanding and designing toolkit solution space, first using qualitative studies to explore mechanisms for simplifying the use and structure of toolkit solution space, and then using a design study of an innovative toolkit. The findings are relevant to innovation and product managers eager to incorporate user ideas with toolkits. Contents Exploring Users Simplifying Solution Space Exploring Structure of Toolkit Solution Space Designing a Toolkit to Generate and Recommend Solutions Simplifying Solution Space for User Innovation and Design Target Groups Researchers and students of information systems and innovation management Innovation managers, product managers and toolkit developers incorporating user ideas The Author Dr. Hari Suman Naik is a postdoctoral researcher at the Friedrich-Alexander-University Erlangen-Nuremberg working with Prof. Dr. Kathrin M. Möslein, Chair of Information Systems I - Innovation & Value Creation.
"Springer Gabler."
Keywords: Computer-aided design.; elektronické knihy; electronic books